The Lesser Pacific Striped Octopus, Octopus chierchiae: An Emerging Laboratory Model - Grearson, Anik G.; Dugan, Alison; Sakmar, Taylor; Sivitilli, Dominic M.; Gire, David H.; Caldwell, Roy L.; Niell, Cristopher M.; Dölen, Gül; Wang, Z. Yan; Grasse, Bret (Frontiers in Marine Science, 2021)
Cephalopods have the potential to become useful experimental models in various fields of science, particularly in neuroscience, physiology, and behavior. Their complex nervous systems, intricate color- and texture-changing body patterns, and problem-solving abilities have attracted the attention of the biological research community, while the high growth rates and short life cycles of some species render them suitable for laboratory culture. Octopus chierchiae is a small octopus native to the central Pacific coast of North America whose predictable reproduction, short time to maturity, small adult size, and ability to lay multiple egg clutches (iteroparity) make this species ideally suited to laboratory culture. Here we describe novel methods for multigenerational culture of O. chierchiae, with emphasis on enclosure designs, feeding regimes, and breeding management. O. chierchiae bred in the laboratory grow from a 3.5 mm mantle length at hatching to an adult mantle length of approximately 20–30 mm in 250–300 days, with 15 and 14% survivorship to over 400 days of age in first and second generations, respectively. O. chierchiae sexually matures at around 6 months of age and, unlike most octopus species, can lay multiple clutches of large, direct-developing eggs every ∼30–90 days. Based on these results, we propose that O. chierchiae possesses both the practical and biological features needed for a model octopus that can be cultured repeatedly to address a wide range of biological questions.